2011
DOI: 10.1177/0886260511425245
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Offenders’ Sex on Reporting Crimes to the Police

Abstract: This article examines the difference in victims' reporting behavior regarding crimes committed by males and by females. The authors expect that victims of female offenders are less likely to report to the police than victims of male offenders because of differences in the victim-offender relationship as well as in the victim's sex. With recent developments in Bayesian statistics, new tools have become available that enable the direct evaluation of researchers' expectations. All cases of robbery with assault fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Although several studies have been conducted to extend our knowledge on the etiologies of crime reporting (Acierno et al, 2001;Baumer, 2002;Boateng, 2015;Boateng & Lee, 2014;Burcar, 2013;Goff, Epstein, & Reddy, 2013;Goudriaan, Lynch, & Nieuwbeerta, 2004;Heath, Lynch, Fritch, & Wong, 2013;Slocum et al, 2010;Tarling & Morris, 2010;Warner, 1992;Wong & Van de Schoot, 2012) and citizens' perceptions of their local police (Boateng, 2012;Kaariainen & Siren, 2011;Rosenbaum, Schuck, Costello, Hawkins, & Ring, 2005;Sunshine & Tyler, 2003;Tyler, 2005), limited research efforts have been directed toward examining the relationship between the two variables (Goudriaan, Nieuwbeerta, & Wittebrood, 2005;Goudriaan, Wittebrood, & Nieuwbeerta, 2006;Watkins, 2005). These limited studies have generally observed that victims' opinions about the police may affect their odds of reporting crime to the institution.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have been conducted to extend our knowledge on the etiologies of crime reporting (Acierno et al, 2001;Baumer, 2002;Boateng, 2015;Boateng & Lee, 2014;Burcar, 2013;Goff, Epstein, & Reddy, 2013;Goudriaan, Lynch, & Nieuwbeerta, 2004;Heath, Lynch, Fritch, & Wong, 2013;Slocum et al, 2010;Tarling & Morris, 2010;Warner, 1992;Wong & Van de Schoot, 2012) and citizens' perceptions of their local police (Boateng, 2012;Kaariainen & Siren, 2011;Rosenbaum, Schuck, Costello, Hawkins, & Ring, 2005;Sunshine & Tyler, 2003;Tyler, 2005), limited research efforts have been directed toward examining the relationship between the two variables (Goudriaan, Nieuwbeerta, & Wittebrood, 2005;Goudriaan, Wittebrood, & Nieuwbeerta, 2006;Watkins, 2005). These limited studies have generally observed that victims' opinions about the police may affect their odds of reporting crime to the institution.…”
Section: Introductionmentioning
confidence: 99%
“…The more serious the crime, the more likely benefits of crime reporting are believed to be, such as enhancing personal safety, reducing fear of crime, retribution against the perpetrator, and the belief that the incident will be successfully pursued within the criminal justice system, will outweigh concerns of wasting police time, feeling ashamed, or even the fear and emotional stress of reenacting the incident (Reyns & Englebrecht, 2010;Skogan, 1976;Tolsma, Blaauw, & Grotenhuis, 2012). Victims may also take a more practical approach when weighing the benefits of reporting to the police: the social obligation to report and contribute to public safety can offset the costs of reaching out to law enforcement (Wong & van de Schoot, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, victimizations perpetrated by known offenders are less likely to be defined as criminal in the first place (Reyns & Englebrecht, 2010): if there is no perceived crime, then there is no need to reach out to law enforcement. Still, a handful of studies have found that victims who know their offenders are more likely to report their victimization to the police (Felson et al, 1999;Goudriaan et al, 2004;Wong & van de Schoot, 2012) thus making the relationship a little less clear. Victims may perceive more benefits in reporting crime when they know the offender if they believe that there is a greater chance of reprisal, or that the police are more likely to catch and punish the known offender.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the individual-level factors included in the current study, only a few were significant. This nonsignificance is surprising in the cases of gender, marital status (single vs. married), and police job rating, which have all been found to be significant predictors for specific crimes among certain international samples (Estienne & Morabito, 2016;Goudriaan et al, 2004;Skogan, 1984) and among studies that only examined personal characteristics and situation-related factors (Avakame et al, 1999;Wong & Van de Schoot, 2012). The fact that these variables were not found to have been significant factors of burglary reporting across the countries included in this research, but have been found to be significant predictors in other research, suggests that their impact varies by country and/or crime type.…”
Section: Results Compared To Existing Literaturementioning
confidence: 97%